2020
DOI: 10.1016/j.nicl.2020.102369
|View full text |Cite
|
Sign up to set email alerts
|

Regional and hemispheric susceptibility of the temporal lobe to FTLD-TDP type C pathology

Abstract: Highlights Anterior temporal lobe (ATL) degeneration is most often caused by FTLD-TDP type C pathology. Cases can present with predominantly left (60%) or right (40%) ATL atrophy. Within ATLs, medial regions are more vulnerable than lateral ones. The observed spectrum of clinical phenotypes is driven by atrophy lateralization. Left and right temporal variants of FTD should be considered the same disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 115 publications
(95 reference statements)
4
48
0
Order By: Relevance
“…In contrast to the previous argument, Borghesani et al, (2020) suggested that the left and the right temporal variant of FTD should be considered the same disease based on their similar neuroanatomical progression patterns within the temporal and contralateral temporal regions[ 50 ]. However, the limitation of that study is that only subjects with TDP type C pathology were included, thereby potentially excluding other underlying pathologies with a different progression pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous argument, Borghesani et al, (2020) suggested that the left and the right temporal variant of FTD should be considered the same disease based on their similar neuroanatomical progression patterns within the temporal and contralateral temporal regions[ 50 ]. However, the limitation of that study is that only subjects with TDP type C pathology were included, thereby potentially excluding other underlying pathologies with a different progression pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitation of that study is that only subjects with TDP type C pathology were included, thereby potentially excluding other underlying pathologies with a different progression pattern. Additionally, it must be noted that most neuropathological studies taking into account the underlying neuropathology of rtvFTD were based on svPPA cohorts[ 20 , 50 ], hence reports of underlying pathology of rtvFTD diagnosed with bvFTD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies additionally support the notion of ALS and FTD as a continuum showing that motor cortex and anterior cingulate as well as their underlying white matter tracts are impacted in ALS patients, while widespread frontal, anterior cingulate, insular, and temporal lobes are impacted in ALS-FTD and bvFTD patients (Lillo et al, 2012;Crespi et al, 2018;Trojsi et al, 2018;Seeley, 2019;Vinceti et al, 2019). Furthermore, while most forms of ALS are due to pathological inclusions of TDP-43 (with some exceptions, noted in the next section), about half of all bvFTD (Neumann et al, 2006;Perry et al, 2017), most svPPA (Grossman, 2010;Josephs et al, 2011;Borghesani et al, 2020), and a portion of nfvPPA cases are due to TDP-43 (Adams-Carr et al, 2020). The other half of bvFTD, a small minority to few svPPA, over half of nfvPPA, CBS, and PSPS result from underlying tau pathology (Josephs et al, 2011).…”
Section: Clinical Phenotypes Of Ftd and Alsmentioning
confidence: 96%
“…The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper. (59, 13 (13,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) FTLD-tau Pick's type 2, (10%) Absent 52 (52,(51)(52)(53) 5 (5,(4)(5)(6) FTLD-TDP-Type-B with MND 1, (5%) Absent 55 9…”
Section: Data Availabilitymentioning
confidence: 99%
“…[5][6][7][8][9] ATL degeneration is typically caused by FTLD-TDP type C and results in a variety of language, behavioral, and emotional symptoms over the course of the illness. Early ATL degeneration is often asymmetric, 10,11 with focal atrophy of either the left ATL (lATL) or right ATL (rATL). Degeneration soon spreads to the opposite hemisphere, and the clinical symptoms that accompany right-and left-predominant syndromes, therefore, often converge over time.…”
Section: Introductionmentioning
confidence: 99%